An Empirical Investigation of Volatility of Indian Spot and Future Prices of Crude Oil. Issue 2 (July 2013) - Chhatwal, Hartika; Puri, Himanshu; Purohit, Harsh
Recent volatility in crude oil prices has affected economies around the world. The paper is focused towards empirically testing the significance in volatility of the spot prices due to future prices of oil commodity in India. The study also investigates the dynamic relationship between both the price series. These interactions, in tum, give rise to publicly reported futures prices that reflect the market's best estimate today of what future supply and demand conditions and, hence, prices will be. The objectives of the study are examined by employing Chow test to check structural break points in prices data, ADF test to check the stationarity, Johansen's co-integration test for examining the long term relationship, and Garch (1, 1) model to check the volatility in spot and the future prices of crude oil. The daily closing data is taken from 1 st May 2005 to 31 st December 2012 for the analysis. Since the period of financial crisis is considered, the entire period (May 2005‐ December 2012) is divided into three sub-periods, namely before crisis period (May 2005‐ August 2008), during crisis (September 2008‐ December 2010) and after crisis period Oanuary 2011‐ December 2012). The findings of the study proved that there are structural break points in the specified data and the series derived from the futures prices and cash market prices for crude oil were not stationary in the level form, but there is evidence of stationarity in the first difference form. Long run relationship between the spot and future price series is also observed. Empirical results also found that in the period during crisis and after crisis there is persistence of high volatility. However, the period before crisis shows less volatility than the other two periods.